2017
DOI: 10.3390/s17071541
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Optical Unobtrusive Blood Pressure Measurements

Abstract: Blood pressure (BP) is critical in diagnosing certain cardiovascular diseases such as hypertension. Some previous studies have proved that BP can be estimated by pulse transit time (PTT) calculated by a pair of photoplethysmography (PPG) signals at two body sites. Currently, contact PPG (cPPG) and imaging PPG (iPPG) are two feasible ways to obtain PPG signals. In this study, we proposed a hybrid system (called the ICPPG system) employing both methods that can be implemented on a wearable device, facilitating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Hybrid techniques have also been developed. Zhang et al [33] proposed a possible smart watch application using contact PPG and iPPG. The smart watch would contain a contact PPG probe for the wrist and a camera to analyze the face for an iPPG when the watch is raised towards head level.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid techniques have also been developed. Zhang et al [33] proposed a possible smart watch application using contact PPG and iPPG. The smart watch would contain a contact PPG probe for the wrist and a camera to analyze the face for an iPPG when the watch is raised towards head level.…”
Section: Discussionmentioning
confidence: 99%
“…This was unexpected as the low-cost aspect of camera-based vital sign estimation was often highlighted in previous reviews 16 17 18 , 20 . Half of those publications made use of dedicated webcams 72 73 74 75 , other types of cameras are regular or “action” camcorders 76 77 78 , DSLRs 79 , and the Microsoft Kinect 80 81 82 . Notably, the public databases DEAP 36 and UBFC-RPPG 27 were also recorded using an inexpensive camcorder/webcam respectively.…”
Section: Survey Taxonomymentioning
confidence: 99%
“…Jeong and Finkelstein presented a work on non-contact blood pressure estimation, in which a consumer-grade high-speed camera was used (Casio EX-FH20, 224x168 pixels at 420 frames per second) 87 . An approach was suggested by Zhang et al, where contact PPG would in the future be fused with PPGI from a smartwatch for blood pressure estimation via pulse transit time 73 , although the presented measurements were performed with a stationary camera. Other groups have evaluated the usage of smartphone cameras for the estimation of HR and RR 88 as well as heart rate variability 89 .…”
Section: Survey Taxonomymentioning
confidence: 99%
“…The physiological signals are recorded with a contact sensor (for measuring wrist signal) and a camera (for measuring face signal), both sensors being embedded in a smartwatch. From [39] Recent studies have demonstrated that PTT can be measured unobtrusively from PPG signals taken at different body sites (Fig.6), like wrist and face using a smartwatch [39] or hand and face using a single video camera [40]. Junior et al [41] have used smartphone camera and microphone to measure PTT: the moment the blood leaves the heart is detected by recording the heart sound with the microphone while the camera is employed to detect the time the blood reaches the finger by analyzing the PPG pulse wave.…”
Section: Blood Pressurementioning
confidence: 99%